Design Thinking for Education Conceptions and Applications in Teaching and Learning - Koh, Joyce Hwee Ling.; Chai, Ching Sing.; Wong, Benjamin; Hong, Huang-Yao.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book explores, through eight chapters, how design thinking vocabulary can be interpreted and employed in educational contexts. The theoretical foundations of design thinking and design in education are first examined by means of a literature review. This is then followed by chapters that characterize design thinking among children, pre-service teachers and in-service teachers using research data collected from the authors$1 (Bdesign-driven coursework and projects. The book also examines issues associated with methods for fostering and assessing design thinking. In the final chapter, it discusses future directions for the incorporation of design thinking into educational settings. Intended for teachers, teacher educators and university instructors, this book aims to provide them with the theoretical foundations needed to grasp design thinking, and to provide examples of how design thinking can be interpreted and evaluated. The materials covered will help these groups of professionals to consider how design thinking can be integrated into their own teaching and learning contexts. The book will also promote a discourse between educational researchers on the theoretical development of design thinking in educational settings.s
Chapter 1 Design Thinking and Education -- Chapter 2 Critical Perspectives on Design & Design Thinking -- Chapter 3 Design Thinking and 21st Century Skills -- Chapter 4 Design Thinking and Children -- Chapter 5 Design Thinking and Pre-service Teachers -- Chapter 6 Design Thinking and In-service Teachers -- Chapter 7 Developing and Evaluating Design Thinking -- Chapter 8 Conclusion.
Keywords: Education; Teaching; Education; Teaching and Teacher Education; Learning & Instruction; Electronic books